Задачи бюджетирования в управлении финансовой деятельностью предприятия - Терещук, И. В. (НТУ "ХПИ", 2013)
In given work is considered the process of forming and motion of material and money streams on an enterprise. Basis of plan of enterprise is made by the order book, formed on the planned period. On the basis of the order book and plan of future activity of enterprise raising of task of budgeting is formulated.
Keywords: планирование оптимальное; портфель заказов; потоки денежные